Performance of the Objective Video Quality Metrics with Perceptual Weighting Considering First and Second Order Differential Operators - Regis, Carlos D. M.; Cardoso, José V. M.; Oliveira, Ítalo P.; Alencar, Marcelo S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Objective video quality assessment is important to validate the performance of applications in video communications systems. The research on visual attention and gradient-inspired metrics improves the performance of the video quality evaluation. This paper investigates the use of first and second order differential operators as visual attention estimators. The edge information, computed by differential operators, is an important factor of visual attention. The performance of the proposed models are compared with the objective metrics, PSNR, SSIM and GSSIM, by means of the Pearson correlation coefficient, considering the blurring, blocking, salt and pepper and Gaussian noise distortions. The results suggest that for blurring, blocking and salt and pepper, the combination of objective metrics with first order operators provides a significant improvement, especially for the Sobel operator.